Reasons for Pregnant Women’s Choice of Elective Caesarean Section - Jassim, Ghufran Nadheer (Journal of Science in Medicine and Life, 2026)
Background: The worldwide rise in cesarean section (CS) rates is becoming a major public health concern and cause of considerable debate due to potential maternal and perinatal risks, cost issues and inequity in access. The Term Caesarean Delivery on Maternal Request (CDMR) refers to elective delivery by caesarean section at the request of a woman with no identifiable medical or obstetric contraindications to an attempt at vaginal delivery. There for Cesarean sections increase the health risks for mothers and infants as well as the costs of health care when they are compared with vaginal birth. Objectives: The study aim to determine the reasons for pregnant women to choose elective caesarean section. Methodology: The descriptive study design was used in this research (quantitative) to determine the reasons for pregnant women to choose cesarean section. The research was conducted at Al- Diwaniyah / Health Directorate of in Maternity and Children Teaching Hospital at Al-Diwaniyah City. The research was conducted from September , 2024 up to March , 2025. A non-probability (purposive) sampling technique was used consisting of (60) pregnant and delivered C/S women and chosen to give birth by caesarean section. An assessment instrument was designed to assess the reasons for pregnant women to choose caesarean section. Results: Findings indicated that the majority of women were chose as a first line of causes (Fear from labor pain and Fear of dystocia) these items account 43(71.7 %) with a mean of score 1.28. Conclusion: The research concluded that fearing from labor pain and fear of dystocia were the main causes that stay behind the women who chose to have C/S. Recommendations: Providing painless NVD in Al Diwaniyah at both public and private maternity hospitals.